1996
DOI: 10.1017/s0022112096000924
|View full text |Cite
|
Sign up to set email alerts
|

Minimum induced power requirements for flapping flight

Abstract: The Betz criterion for minimum induced loss is used to compute the optimal circulation distribution along the span of flapping wings in fast forward flight. In particular, we consider the case where flapping motion is used to generate both lift (weight support) and thrust. The Betz criterion is used to develop two different numerical models of flapping. In the first model, which applies to small-amplitude harmonic flapping motions, the optimality condition is reduced to a one-dimensional integral equation whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 10 publications
1
73
0
Order By: Relevance
“…More recently, the problem of apping foil propulsion has been considered by L i u 17 18 using vortex lattice and panel methods, by Send 19 20 using linearized theory and by Hall and Hall 21 and Hall et al 22 using vortex lattice methods.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the problem of apping foil propulsion has been considered by L i u 17 18 using vortex lattice and panel methods, by Send 19 20 using linearized theory and by Hall and Hall 21 and Hall et al 22 using vortex lattice methods.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the problem of apping foil propulsion has been considered by L i u 17 18 using vortex lattice and panel methods, by Send 19 20 using linearized theory and by Hall and Hall 21 and Hall et al 22 using vortex lattice methods. Jones et al 7 compared wake structures behind apping wings experimentally photographed and numerically predicted, and demonstrated that the formation and evolution of these unsteady wakes is essentially an inviscid phenomenon over a broad range of Strouhal numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Others, such as Hall and Hall 7 and Wang, 5 have approached the problem from a different viewpoint by taking well-developed computer models of flapping flight and trying to predict optimum flapping parameters. In nature, flapping frequency selection must be based on biology and physics.…”
Section: Biology-based Workmentioning
confidence: 99%